Konsep Konseling Lintas Budaya - Anton Widodo; Andi Rahmad; Evy Septiana Rachman (Institut Agama Islam Negeri Padangsidimpuan, 2022)
In the field of counseling and psychology, the cross-cultural approach is seen as a fourth force after the psychodynamic, behavioral and humanistic approaches. Many authors who write about cross-cultural counseling are often from their own minority populations, interpreting them differently as the diversity and cultural differences. In cross-cultural counseling, the relationship between the counselor and the counselee is involved. However, the relationship that occurs in counseling is a relationship in a human situation, meaning that both the counselor and the client are human beings with their own characteristics, both personality characteristics and the characteristics of the values, morals and culture each carries. respectively. Thus the counseling relationship is not simple. Counselors must be aware of the differences in characteristics (personal, values, morals, culture) between themselves and their clients, and respect the uniqueness of their clients. These differences, however, will affect the counseling process. This is where the need for cross-cultural counseling, namely counseling that accommodates cultural differences between counselor and client. Counseling with cross-cultural insight is effective in eliminating the possibility of counselor behavior that uses its own culture (counselor encapsulation) as a reference in the counseling process.